Terapi Yoga Untuk Mengurangi Nyeri Punggung Pada Ibu Hamil - Nur Hidayatul Ainiyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Pregnancy back pain relates to mobility, lifting technique, sleep quality and pattern, and sexual activity. The impacts of low back pain in pregnancy include insomnia, decreased productivity, stress, depression, difficulty standing up, pain that interferes with daily activities, increased use of pain medication, and even the risk of developing chronic back pain. Currently, complementary and alternative medicine is a concern for people worldwide in reducing pain complaints based on their usefulness and safety values. Yoga is a complementary and alternative medicine that combines several poses (asanas), breathing (pranayama), and relaxation. This study aims to determine the effect of prenatal yoga in reducing complaints of low back pain in pregnant women.Methods: The design of this study was quasi-experimental with a pre-test post-test approach with control group design. This research was conducted at TPMB Sri Wahyuni in June - August 2022. The target population of this study was all pregnant women with low back pain in Surabaya. The sampling technique used is purposive sampling. The sample in this study was 40 people (consisting of 20 people in the control group and 20 in the intervention group). The instrument used to measure low back pain is the Visual Analog Scale (VAS). Data were analyzed using paired T-test.Results: The characteristics of the research subjects in the intervention and control groups did not show a significant difference. The age of the youngest research subject is 18 years, and the oldest is 34 years. There were four subjects with obesity in the prenatal yoga group and seven people in the control group. In both the intervention group and the control group, the majority of mothers are not working. Data analysis using Paired T-Test in the prenatal yoga group showed that prenatal yoga reduced low back pain because p<0.001.Conclusion: Pregnant yoga intervention effectively reduces low back pain in pregnant women.